The impact of quota rent and supply elasticity estimates for EU dairy policy evaluation: a comparative analysis - Roel Jongeneel; Axel Tonini (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2009)
The aim of this paper is to gain better insights in the implications of some of the most important economic assumptions and empirical choices made in partial equilibrium models focusing on dairy. Three partial equilibrium models are considered: the AGricultural Member states MODeling (AGMEMOD) model, the Common Agricultural Policy SIMulation (CAPSIM) model, and the European Dairy Industry Model (EDIM). This paper analyses how quota rent and supply elasticity estimates, as they are used in these models affect milk output and price projections. Sensitivity analysis is also considered in order to take into account uncertainty in quota rent and supply elasticity estimates. Taking into account the considered uncertainty our best estimate is in case of abolishing the quota the EU's aggregate milk production will expand, with the increase being somewhere in the range between 5 and 15%. – – Das Ziel dieses Beitrags ist es, am Beispiel des Milchmarkts die Auswirkungen wichtiger ökonomischer Annahmen in partiellen Gleichgewichtsmodellen zu untersuchen. Wir beziehen drei Modelle in die Analyse ein: das Agricultural Member states MODeling (AGMEMOD)-Modell, das Common Agricultural Policy SIMulation (CAPSIM)-Modell sowie das European Dairy Industry Model (EDIM). Untersucht wird der Einfluss von Annahmen über die Quotenrenten und die Angebotselastizitäten, wie sie in diesen Modellen zwecks Projektion der Milchmenge und des Milchpreises getroffen werden. Der Unsicherheit bei der Schätzung von Quotenrenten und Angebotselastizität wird durch Sensititätsanalysen Rechnung getragen. Unter Berücksichtigung der bestehenden Unsicherheit lautet die beste Schätzung für den Fall der Abschaffung der Milchquote, dass die Milcherzeugung in der EU in einem Umfang von 5 bis 15 % ausgedehnt werden wird (Quelle: Verlag).
Keywords: 330; Milchmarkt; Gemeinsame Marktorganisation; Milchpolitik; Partielles Gleichgewicht; Preiselastizität; EU-Staaten